EFFECT OF GINGER AND ROSEMARY EXTRACTS AS ANTIOXIDANT AND ANTIBACTERIAL AGENTS IN TILAPIA FISH FINGERS - Biassi, Deise Caroline; Schlichting da Silva, Larissa; Alves Delfino, Larissa; de Oliveira, Jaqueline; Tormen, Luciano; Molardi Bainy, Eduarda (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
This work aimed to evaluate the antioxidant and antibacterial effects of commercial ginger and rosemary extracts on tilapia fish fingers during frozen storage. Three formulations of fish fingers using tilapia mechanically separated meat (MSM) were produced with 2.5 % of hydroalcoholic ginger extract (GE), 2.5 % of oily rosemary extract (RE) and a control. pH, instrumental color, peroxide value (PV), determination of thiobarbituric acid reactive substances (TBARS), and sensorial evaluation with a trained panel, were carried out monthly during 120 days of frozen storage. Total mesophilic and Enterobacteriaceae counts were conducted at the beginning and the end of storage. pH remained near 6.0. GE showed a darker color (lower L*) at the end of the study. PV reduced with storage time, however, there was no difference among formulations. RE had the lowest TBARS value at 120 days. GE became with an unacceptable flavor and had the highest TBARS value at the end of frozen storage. There was a little reduction in the bacteria counts for the products with extracts. Rosemary extract was more efficient in reducing the lipid oxidation of frozen fish fingers than ginger extract.